Effect of panel method codes in estimating the time-domain responses of floating wind turbines - Muhammed Ucar; Mohamad Hmedi; Emre Uzunoglu; Elif Oguz (Brodogradnja)
This study investigates the impact of frequency-domain hydrodynamic outputs from several panel method codes on estimating time domain responses of floating wind turbines. The tools under examination are WAMIT and three open-source codes (HAMS, NEMOH, and BEMUse). The panel method codes deliver hydrodynamic coefficients and exciting forces in the frequency domain. The results serve as inputs to time-domain simulations, from which the coupled responses are calculated. Hence, the differences in frequency-domain inputs are reflected in the time-domain. Two platforms are employed: OC3-Hywind spar and OC4-DeepCWind semi-submersible. Discrepancies between hydrodynamic coefficients, excitation forces, and response amplitude operators are inspected. Then, the floaters’ time-domain responses are questioned in operational and extreme environmental conditions. The findings highlight limited reflection of frequency-domain differences on the platform motions in time-domain.